1996
DOI: 10.1093/oxfordjournals.jbchem.a021466
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ Signaling and Intracellular Ca2+ Binding Proteins

Abstract: Changes in cytosolic Ca2+ concentrations evoke a wide range of cellular responses and intracellular Ca(2+)-binding proteins are the key molecules to transduce Ca2+ signaling via enzymatic reactions or modulation of protein/protein interations (Fig.1). The EF hand proteins, like calmodulin and S100 proteins, are considered to exert Ca(2+)-dependent actions in the nucleus or the cytoplasm. The Ca2+/phospholipid binding proteins are classified into two groups, the annexins and the C2 region proteins. These protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
77
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(77 citation statements)
references
References 115 publications
(130 reference statements)
0
77
0
Order By: Relevance
“…On the basis of the primary structures responsible for the actual binding of these domains, intracellular Ca 2ϩ -binding proteins can be classified in the following three categories: EF-hand proteins, Ca 2ϩ /phospholipid-binding proteins (annexins and C2 region proteins), and Ca 2ϩ storage proteins (e.g. calsequestrin, calreticulin) (53). We have compared the typical sequence motifs of these three categories of Ca 2ϩ -binding proteins with the Ca 2ϩ -binding regions that we have detected in the InsP 3 R. None of the regions showed resemblance with known motifs.…”
Section: ] Was Gradually Increased (Closed Circles) or Decreased (Opementioning
confidence: 99%
“…On the basis of the primary structures responsible for the actual binding of these domains, intracellular Ca 2ϩ -binding proteins can be classified in the following three categories: EF-hand proteins, Ca 2ϩ /phospholipid-binding proteins (annexins and C2 region proteins), and Ca 2ϩ storage proteins (e.g. calsequestrin, calreticulin) (53). We have compared the typical sequence motifs of these three categories of Ca 2ϩ -binding proteins with the Ca 2ϩ -binding regions that we have detected in the InsP 3 R. None of the regions showed resemblance with known motifs.…”
Section: ] Was Gradually Increased (Closed Circles) or Decreased (Opementioning
confidence: 99%
“…Many calcium-mediated effects have been well characterized in other systems (Carafoli, 1987;Heizman and Hunziker, 1991;Ikura, 1996;Niki et al, 1996). In these cases, the physiological effects of calcium are often mediated indirectly by signal proteins.…”
mentioning
confidence: 99%
“…By binding calcium, these proteins undergo conformational changes that enable interaction with and modulation of effector proteins that cause the physiological changes linked to the calcium stimulus. Many of these calcium-signal proteins are well characterized and have been subgrouped based on structural and biochemical features (Heizman and Hunziker, 1991;Nakayama and Kretsinger, 1994;Niki et al, 1996). The majority are intracellular constituents, but some members may be secreted and have intercellular actions (Zimmer et al, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular calcium ions (Ca 2+ ) is very important in morphogenesis (Niki et al, 1996; Berridge, (Tsuruwaka et al, 2007(Tsuruwaka et al, & 2016. We also reported that morphological changes brought about 35 dramatic transition in Ca 2+ signaling (Tsuruwaka, Konishi & Shimada, 2015 …”
mentioning
confidence: 95%